A qualitative study to discover the future scope and barriers towards facilitating animals-assisted therapy (AAT)for autisitic children in Macau (China) - Das Neves Chiang, Sara Violeta (2015)
This qualitative study seeks to discover the future scope of developing animal-assisted therapy (AAT) in Macau (China) based on the local parents’ perspectives. Social aversion in children with autism tends to be human-specific thus does not take into account of therapy animals, which can offer calming and nonjudgmental support thus enhancing and encouraging social interactions in children with autism. The aims of this paper include evaluating current evidence on how AAT can support the domains of social interaction and/or communication in autistic children, and exploring the future scope of facilitating AAT in Macau based on parents’ perspectives using semi-structured interviews. Thematic analysis was used to analyse the findings and identified 4 themes: 1) parents’ negative attitudes to society, 2) parents’ opinions towards animals in general, 3) parents’ opinions towards AAT and 4) factors to consider towards AAT in the future. Overall, parents showed support towards the implementation of AAT despite the need to overcome potential barriers. Recommendations will be made on facilitating AAT in Macau in the future, as well as directions for future research. Keywords: Animal-assisted therapy (AAT), human-animal interactions (HAI), human-animal companionships, autism, social interaction, communication, semi-structured interviews